Coagulation Using Aloe Vera Gel and Coconut Shell Charcoal Filtration To Reduce Iron in Parit Banjar River Water - Fara Chitra; Syarifah Wiwika; Hajimi Hajimi (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2026)
River water in the Parit Banjar area, Pontianak, contains iron (Fe) levels that exceed acceptable limits for hygiene and sanitation use. This study aimed to evaluate the efficiency of a combined treatment using Aloe vera gel as a natural coagulant and coconut shell charcoal as a filtration medium to reduce Fe concentration in river water. This study employed a quasi-experimental pretest-posttest design with a control group. Raw river water samples were treated with 40 grams of Aloe vera gel, stirred at 40 rpm for 2 minutes, allowed to stand for 60 minutes, and then filtered through coconut shell charcoal media with thickness variations of 60, 70, 80, 90, and 100 cm. Each treatment was repeated five times. Fe concentration was measured before and after treatment, and removal efficiency was calculated descriptively. The mean initial Fe concentration was 4.32 mg/L, while the control group showed a mean of 4.18 mg/L. Coagulation using Aloe vera gel alone reduced Fe to 3.56 mg/L with an efficiency of 17.44%. The combined treatment produced greater reductions at all filter thicknesses. The best result was obtained at 100 cm, reducing Fe to 0.55 mg/L with an efficiency of 87.36%. Increasing filter thickness consistently improved Fe removal. The combination of Aloe vera gel coagulation and coconut shell charcoal filtration was effective at reducing the Fe concentration in the Parit Banjar river water. A thicker filtration medium provided better removal performance, with 100 cm identified as the most effective condition.